Raw Material Inventory Control in Frozen Street Food SMEs: Applications of JIT and MRP Techniques - Agustina Senjayani; Devi Novera; Dewi Rohma Wati (International Journal of Economics, Business and Innovation Research, 2025)
Food SMEs still encounter multiple challenges in managing their raw materials, exemplified by ABC Cireng Factory, a small and medium-sized enteprise in the frozen processed street food sector located in Depok City, dealing with issues such as recurring supruses of tapioca flour raw materials, causing cost inefficiencies and irregularities in order frequencies and quantities monthly. This study aims to assess the inventory management of tapioca flour raw materials at the ABC Cireng Factory by utilizing the company's approach alongside the Just in Time (JIT) and Material Requirement Planning (MRP) methods; to compare all these methods, and ultimately, to suggest a more effective inventory control approach suitable to be implemented. The study reveals that the company's approach results in a total cost of tapioca flour raw material inventory amounting to IDR 11,197,514,500, with an annual raw material purchase of 525,400 kg and an order frequency of 200 times. Using the JIT approach, the overall inventory expense reaches IDR 35,667,065, with a single order size of 1,035 kg and an order frequency of 502 occurrences. In the MIDR approach utilizing the Lot for Lot (LFL) method, the overall inventory cost amounts to IDR 10,067,554,320, featuring a total raw material inventory of 474,950 kg annually and an order frequency of 44 times. With the MIDR method utilizing the Economic Order Quantity (EOQ) approach, the overall inventory cost amounts to IDR 10,790,524,400 for an order quantity of 50,976 kg and an order frequency of 10 occurrences. The MIDR approach utilizing the LFL technique is the most appropriate method for implementation at the ABC Cireng Factory.